New Determination Method of Two Bioactive Saponins in Lysimachia capillipes Hemsl. by Quantitative Analysis of Multi-Components by Single-Marker. (17th March 2021) - Zhang, Xiaoyong; Chen, Xuezhao; Jin, Juan; Gong, Minghua; He, Qiang; Li, Shouxin; Tian, Jinkui
Abstract: Capilliposide B (CPS-B) and Capilliposide C (CPS-C), as the key components in Lysimachia capillipes Hemsl., increasingly aroused the interest and research concern of many researchers due to the good bioactivities. Nowadays, the reference standards of CPS-B and CPS-C yield were very limited. Due to the deficit of reference standards, the determination could be difficult to carry out, and the quality control and evaluation would be restrained afterwards. To solve this urgent problem, a quantitative analysis of multi-components by single-marker (QAMS) method was proposed and established based on high-performance liquid-chromatography tandem evaporative light-scattering detector. In this QAMS method, the content of the two bioactive components could be calculated by buddlejasaponin IV, which is applied as an external standard and readily obtained. And the methodological experiments were evaluated and indicated accuracy, stability and feasibility of this QAMS method. Therefore, in this study, this built method would properly meet the requirement of determination of CPS-B, CPS-C and quality control of the L. capillipes Hemsl. plant.